Viral Infections in the Modern Era: Advances in Medical Microbiology and Diagnostic Approaches - Monga, Rubina (Journal of Neonatal Surgery, 2025)
Viral infections continue to pose significant global health challenges, necessitating rapid and accurate diagnostic approaches. This review explores the evolution of viral diagnostics, from early culture-based techniques to modern molecular tools such as PCR, isothermal amplification, and CRISPR-based assays. It also highlights advancements in immunological methods, biosensors, and non-invasive testing. The integration of artificial intelligence, nanotechnology, and digital health platforms has further revolutionized point-of-care testing and outbreak surveillance. While these innovations enhance diagnostic capabilities, issues like scalability, cost, and adaptability to viral mutations remain. Addressing these challenges is crucial for developing effective, accessible, and resilient diagnostic systems. Emerging technologies promise to bridge diagnostic gaps, especially in low-resource settings. A multidisciplinary approach will be key to driving future innovation and preparedness against viral threats.